COMMUNICATION MANAGEMENT IN OPTIMIZING THE FUNCTION OF MOSQUES AS COMMUNITY DEVELOPMENT CENTERS: A CASE STUDY OF THE MANAGEMENT OF THE GREAT MOSQUE AND THE GREAT MOSQUE IN THE CITY OF MEDAN - Muslim Muslim; Lies Utami Efni Safitri; M. Taufiq Hidayah Tanjung (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the application of communication management in optimizing the function of the Great Mosque and the Great Mosque of Medan City as a center for community development. The research uses a descriptive qualitative approach by collecting data through observation and in-depth interviews with the management of the Mosque Prosperity Agency (BKM), secretariat staff, and active worshippers of the two mosques. Secondary data was obtained from literature reviews in the form of books, journals, and official documents related to communication management and mosque management. The results of the study show that effective communication is the main key in optimizing the function of the mosque. The mosque management implements careful communication planning, organizes communication through clear division of tasks and coordination channels, implements communication with direct and digital channels, and controls and evaluates communication to assess the success of the program. Communication strategies that are clear, simple, friendly, and actively involve worshippers have been proven to increase community participation, make mosques more lively, and function not only as a place of worship but also as a center for social development, education, and da'wah. These findings corroborate that good communication management is able to make mosques an effective and sustainable community development center.